Case Report: Recognition and management of SMARCA4-deficient renal cell carcinoma - Wang, Weibo; Yin, Shuiping; Xu, Dandan; Tai, Supeng; Cheng, Xi; Chang, Yifan; Fu, Yao; Zhou, Jun (Frontiers in Oncology, 2025)
SMARCA4-deficient tumors represent a highly aggressive subtype of malignancy defined by the loss of SMARCA4 expression, and are associated with rapid progression and poor prognosis. We report the first documented case of SMARCA4-deficient renal cell carcinoma (RCC) in an adult (pT3aN1M1, Stage IV), characterized by sarcomatoid and rhabdomyoblastic differentiation, aggressive clinical behavior, and resistance to standard systemic therapies. This case provides a comprehensive analysis of clinical, pathological, imaging, and genetic findings, offering insights to refine diagnostic, therapeutic, and preventive strategies for this rare malignancy.